Dual surgeon operating to improve patient safety. Issue 7 (September 2021) - Ellis, R.; Hardie, J.A.; Summerton, D.J.; Brennan, P.A.
Abstract: The COVID-19 pandemic resulted in an unprecedented reduction in the delivery of surgical services worldwide, especially in non-urgent, non-cancer procedures. A prolonged period without operating (or 'layoff period') can result in surgeons experiencing skill fade (both technical and non-technical) and a loss of confidence. While senior surgeons in the UK may be General Medical Council (GMC) validated and capable of performing a procedure, a loss of 'currency' may increase the risk of error and intraoperative patient harm, particularly if unexpected or adverse events are encountered. Dual surgeon operating may mitigate risks to patient safety as surgeons regain currency while returning to non-urgent operating and may also be beneficial after the greatly reduced activity observed during the COVID-19 pandemic for low-volume complex operations. In addition, it could be a useful tool for annual appraisal, sharing updated surgical techniques and helping team cohesion. This paper explores lessons from aviation, a leading industry in human factors principles, for regaining surgical skills currency. We discuss real and perceived barriers to dual surgeon operating including finance, training, substantial patient waiting lists, and intraoperative power dynamics.